Decision Support Models for Movies: Making Science out of an Art - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
Can movie exhibitors, distributors and producers predict box office earnings apart from opening numbers, some good hunches, and a lot of luck? At a recent seminar on ‘Researching the Entertainment Industry’ at the Singapore Management University, Josh Eliashberg, Wharton professor of marketing and operations and information management, presented a set of decision support tools developed with an international team of researchers, which could help “to make a science out of an art”.